Environmental and genetic determinants of transcriptional plasticity in Chinook salmon. (January 2018) - Wellband, Kyle; Heath, John; Heath, Daniel
Abstract Variation in gene transcription is widely believed to be the mechanistic basis of phenotypically plastic traits; however, comparatively little is known about the inheritance patterns of transcriptional variation that would allow us to predict its response to selection. In addition, acclimation to different environmental conditions influences acute transcriptional responses to stress and it is unclear if these effects are heritable. To address these gaps in knowledge, we assayed levels of messenger RNA for 14 candidate genes at rest and in response to a 24-h confinement stress for 72 half-sib families of Chinook salmon reared in two different environments (hatchery and semi-natural stream channel). We observed extensive plasticity for mRNA levels of metabolic and stress response genes and demonstrated that mRNA level plasticity due to rearing environment affects mRNA level plasticity in response to stress. These effects have important implications for natural populations experiencing multiple stressors. We identified genotype-by-environment interactions for mRNA levels that were dominated by maternal effects; however, mRNA level response to challenge also exhibited a non-additive genetic basis. Our results indicate that while plasticity for mRNA levels can evolve, predicting the outcome of selection will be difficult. The inconsistency in genetic architecture among treatment groups suggests there is considerable cryptic genetic variation for gene expression.